Persuasive Messages in Stunting Prevention Efforts in Koto Tangah Nagari, West Pasaman Regency - Muhammad Asyraf; Yayuk Lestari; Annisa Anindya (Ilomata International Journal of Social Science, 2026)
Stunting remains a major public health challenge in Indonesia, particularly in West Pasaman. This qualitative case study utilizes the Elaboration Likelihood Model (ELM) to examine how stunting prevention messages are processed by caregivers in Nagari Koto Tangah. Data were gathered through interviews with mothers, cadres, and midwives, along with observations and documentation. The study identifies two primary processing routes. Most participants follow the peripheral route, where message acceptance is driven by trust in familiar figures (midwives and cadres), social proximity, or external incentives like social assistance (PKH) requirements. A smaller group engages in central processing, typically those with higher education or personal experience with child nutrition issues. Key findings suggest that technical jargon like "stunting" often hinders understanding. In contrast, everyday language (e.g., "malnutrition" or "small body"), concrete examples, and direct face-to-face interaction facilitate deeper comprehension and a greater intent to act. Face-to-face communication proved more effective than static materials like posters. However, several barriers to effective communication persist, including crowded service environments, limited opportunities for dialogue, one-way information flow, and household dynamics—such as husbands' resistance to immunization. Additionally, attendance is frequently motivated by social assistance rather than health awareness. The study concludes that effective health communication in rural contexts depends on trusted messengers delivering localized, interactive, and actionable content. This approach encourages caregivers to move beyond passive routine toward meaningful engagement with stunting prevention.